PENGALIHAN ATAS HARTA WARISAN YANG DILAKUKAN OLEH SALAH SEORANG AHLI WARIS TANPA PERSETUJUAN AHLI WARIS YANG LAIN (Studi Putusan MA Nomor 234 PK/Pdt/2004) - DARJI SAFUTRA (PREMISE LAW JURNAL, 2016)
Inheritance problem will be experienced by most people if one of them dies; therefore, inheritance law is very important for human beings, especially heirs since it is related to the heirs’ survival and needs. Inheritance Law includes three components: the property, the testator, and the heir who receives the transfer or the distribution of inheritance. Besides that, inheritance exists because of death, inheritance by will, and inheritance without will. The problem will exist when there is a delay in distributing inheritance. The research problems were the position of heir in the Inheritance law in Indonesia and how about writing inheritance right certificate. The research used descriptive analytic method with the approach or approval of transferring inheritance. Secondary data were gathered by compiling primary, secondary, and tertiary legal materials. Keywords:  Transferring Inheritance, Done Heir only, without the other Heirs